Non-carbonic buffer power of whole blood is increased in experimental metabolic acidosis: An in-vitro study - Krbec, Martin; Waldauf, Petr; Zadek, Francesco; Brusatori, Serena; Zanella, Alberto; Duška, František; Langer, Thomas (Frontiers in Physiology, 2022)
Non-carbonic buffer power (βNC) of blood is a pivotal concept in acid-base physiology as it is employed in several acid-base evaluation techniques, including the Davenport nomogram and the Van Slyke equation used for Base excess estimation in blood. So far, βNC has been assumed to be independent of metabolic acid-base status of blood, despite theoretical rationale for the contrary. In the current study, we used CO2 tonometry to assess βNC in blood samples from 10 healthy volunteers, simultaneously analyzing the electrolyte shifts across the red blood cell membrane as these shifts translate the action of intracellular non-carbonic buffers to plasma. The βNC of the blood was re-evaluated after experimental induction of metabolic acidosis obtained by adding a moderate or high amount of either hydrochloric or lactic acid to the samples. Moreover, the impact of βNC and pCO2 on the Base excess of blood was examined. In the control samples, βNC was 28.0 ± 2.5 mmol/L. In contrast to the traditional assumptions, our data showed that βNC rose by 0.36 mmol/L for each 1 mEq/l reduction in plasma strong ion difference (p < 0.0001) and was independent of the acid used. This could serve as a protective mechanism that increases the resilience of blood to the combination of metabolic and respiratory acidosis. Sodium and chloride were the only electrolytes whose plasma concentration changed relevantly during CO2 titration. Although no significant difference was found between the electrolyte shifts in the two types of acidosis, we observed a slightly higher rate of chloride change in hyperchloremic acidosis, while the variation of sodium was more pronounced in lactic acidosis. Lastly, we found that the rise of βNC in metabolic acidosis did not induce a clinically relevant bias in the calculation of Base excess of blood and confirmed that the Base excess of blood was little affected by a wide range of pCO2.